Жінка в житті та творчості Івана Яковича Франка - Покотило, К.С.; Школенко, Д.В. (Культура народов Причерноморья, 2013)
Життя та творча діяльність видатного українського письменника Івана Яковича Франка впродовж багатьох років знаходиться в центрі уваги літературознавців. У статті розглядаються особливості життєвого та творчого шляху Івана Яковича Франка. Здійснюється спроба проаналізувати вплив і роль стосунків з жінками в житті та творчості митця, дати правдиву характеристику найбільш впливовим жінкам, які відіграли неоціниму роль у становленні його як митця світового рівня. Актуальність дослідження зумовлена тим, що ця тема довгі роки розглядалась в контексті інших питань, незважаючи на те, що саме стосунки з жінками надихали Франка на вибір тем для своїх творів, полегшували пережиті життєві негаразди. Об’єктом дослідження є спілкування Франка з чотирма жінками, в яких він закохувався, і які залишили пам'ять у його серці на довгі роки. Жизнь и творческая деятельность известного украинского писателя Ивана Яковлевича Франка находится в центре внимания литературоведов на протяжении многих лет. В статье рассматриваются особенности жизненного и творческого пути Ивана Яквлевича Франка. Осуществляется попытка проанализировать влияние и роль взаимоотношений с женщинами в жизни и творчестве писателя, дать правдивую характеристику наиболее влиятельным женщинам, которые сыграли неоценимую роль в становлении его как писателя мирового уровня. Life and creative activity of famous Ukrainian writer Ivan Yakovich Franko is in the center of literary scholars’ attention for many years. The article considers the peculiarities of Ivan Yakovich Franko’s life and creative way. An attempt to analyze the influence and role of relations with women in writer’s life and creative activity, to give the truthful characteristics of the most influential women, who played invaluable role in becoming him as a writer of the world level, is fulfilled. Ivan Yakovich Franko is a famous poet, prose writer, playwriter, literary critic, publicist, translator and scientist. He was not only a capable writer but comprehensively talanted person. He is called the poet-fighter but his soul, as everybody’s one, had place for love – the highest feeling. The actuality of investigation is caused by the fact that this theme was considered in the context of the other questions for many years, despite that relations with women inspired Franko for choosing the themes for his works, made easier life problems and turmoils. The object of investigation is Franko’s communication with four women, whom he fell in love with, and who left the memory in his heart for long years.